Mindfulness - Martínez, José; Bautista, Salvador (CIEX JOURNAL, 2017)
Mindfulness. It is a world that did not exist in our vocabulary until recently. How would we know about that word? The explanation is not as hard as we thought. The first word that came to our mind was mind full of something. We did not know what exactly, but we knew it had something to do with doing positive things.